Analisis Kesiapan Sumber Daya Manusia dalam Menghadapi Transformasi Digital: Studi Kasus pada RSUD Jombang - wasis (PT. Karya Inovatif Nusantara, 2026)
The rapid development of technology requires healthcare institutions to adapt through digital transformation. This study aims to analyze the readiness of human resources (HR) at RSUD Jombang in facing digital transformation, specifically focusing on the influence of digital literacy and organizational support. A quantitative descriptive method was utilized, gathering data from 150 healthcare and administrative staff via structural questionnaires. The collected data were analyzed using multiple linear regression techniques. The results indicate that both digital literacy and organizational support significantly and positively influence employee readiness for digital transformation, with organizational support emerging as the primary driver. To ensure a seamless transition, it is highly recommended that management design structured and continuous digital training programs, alongside upgrading the internal technological infrastructure. This proactive approach will help mitigate resistance and build a digitally competent workforce capable of maintaining high standards of patient care. In the long term, sustainable digital readiness among healthcare professionals will directly contribute to enhanced patient safety, reduced administrative overhead, and optimized medical services in regional public hospitals.